ZONA EKONOMI EKSLUSIF (ZEE) DALAM POROS MARITIM DAN TOL LAUT - Joko Dwi Sugihartono (UNIMAR AMNI Semarang, 2018)
in Indonesia is a region bordering the sea region of Indonesia determined by the law which included sea bed, land under it and water above it with the limit of 200miles. This is measured from Indonesian line of the sea.This whole time a lot of people see the shoreline as the sea border. This perspective makes us alienated and lack of knowledge to take advantage of the sea. This understanding also conjures the idea sea toll, to confirm that Indonesia is maritime country. Sea toll means building sea transportation with ships or sea logistic system which will serve nonstop back and forth from Sabang to Merauke. One of the factors to support this is by building ports (deep sea port) order to give faraway to big ships. A course that spreading as far as 5,000 kilometers or an eighth circumference of the earth One of the purposes of sea toll is to move the economy as efficient and evenly as possible. With the hope that, there will be ships back and forth on Indonesian water, so logistics cost will be cheap. That is why; sea toll is one of President Joko Widodo’s priorities which are also meant to develop Indonesia as maritime country and develop Indonesia as national unity. In addition sea toll can also be affirmation, that Indonesia is in every regions even if it is through ships.Keywords : Exclusive Economic Zone (ZEE) , Sea Toll , The Shaft Maritime, A Seaport